Activation of Endothelial Nitric Oxide (eNOS) Occurs through Different Membrane Domains in Endothelial Cells. - Jason Tran; Astrid Magenau; Macarena Rodriguez; Carles Rentero; Teresa Royo; Carlos Enrich; Shane R Thomas; Thomas Grewal; Katharina Gaus (PLoS ONE, 2016)
Endothelial cells respond to a large range of stimuli including circulating lipoproteins, growth factors and changes in haemodynamic mechanical forces to regulate the activity of endothelial nitric oxide synthase (eNOS) and maintain blood pressure. While many signalling pathways have been mapped, the identities of membrane domains through which these signals are transmitted are less well characterized. Here, we manipulated bovine aortic endothelial cells (BAEC) with cholesterol and the oxysterol 7-ketocholesterol (7KC). Using a range of microscopy techniques including confocal, 2-photon, super-resolution and electron microscopy, we found that sterol enrichment had differential effects on eNOS and caveolin-1 (Cav1) colocalisation, membrane order of the plasma membrane, caveolae numbers and Cav1 clustering. We found a correlation between cholesterol-induced condensation of the plasma membrane and enhanced high density lipoprotein (HDL)-induced eNOS activity and phosphorylation suggesting that cholesterol domains, but not individual caveolae, mediate HDL stimulation of eNOS. Vascular endothelial growth factor (VEGF)-induced and shear stress-induced eNOS activity was relatively independent of membrane order and may be predominantly controlled by the number of caveolae on the cell surface. Taken together, our data suggest that signals that activate and phosphorylate eNOS are transmitted through distinct membrane domains in endothelial cells.